z
- 4
x
1
+
x
2
= 0
-12
x
1
+ 6
x
2
+
x
3
= 6
4
x
1
- 4
x
2
+
x
4
= 4
1
-4
1
0
0
0
0
-12
6
1
0
6
0
4
-4
0
1
4
Initial Simplex Table
Sec 2.7
Friday, February 05, 2010
8:07 PM
Section2dot7 Page 1

This
** preview**
has intentionally

**sections.**

*blurred***to view the full version.**

*Sign up*
z
- 4
x
1
+
x
2
= 0
-12
x
1
+ 6
x
2
+
x
3
= 6
4
x
1
- 4
x
2
+
x
4
= 4
Initial Simplex Table
pc
1
-4
1
0
0
0
0
-12
6
1
0
6
0
4
-4
0
1
4
pivot entry is
4
because it is
the only positive entry in pc
R'
3
= 1/4 R
3
,
R'
1
= R
1
+ 4R'
3
,
R'
2
= R
2
+ 12R'
3
2.7.1
Friday, February 05, 2010
8:07 PM
Section2dot7 Page 2